2012
DOI: 10.4315/0362-028x.jfp-12-183
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genotypic and Antimicrobial Susceptibility Analysis of Zoonotic Campylobacter Species Isolated from Broilers in a Nationwide Survey, Portugal

Abstract: Campylobacter is a major cause of human foodborne disease worldwide and has been associated with the consumption of contaminated poultry. The prevalence of Campylobacter species in broiler flocks from more than 200 producers widespread in mainland Portugal was assessed in 2008 in response to Commission Decision 2007/516/EC. Campylobacter isolates were obtained from 83.3% of 424 pooled cecal samples, with a higher prevalence of Campylobacter coli (61.2%) than Campylobacter jejuni (38.8%). Restriction fragment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
(36 reference statements)
2
3
0
1
Order By: Relevance
“…We also found higher AMR in Campylobacter from chicken isolates on organic farms in Portugal, the UK, and some parts of the US. These findings mirror previous research that has also found higher AMR in Campylobacter on chicken farms in the UK and Portugal 34,35 and suggests that organic farming practices might not necessarily reduce consumer risk of exposure to Campylobacter.…”
Section: Discussionsupporting
confidence: 88%
“…We also found higher AMR in Campylobacter from chicken isolates on organic farms in Portugal, the UK, and some parts of the US. These findings mirror previous research that has also found higher AMR in Campylobacter on chicken farms in the UK and Portugal 34,35 and suggests that organic farming practices might not necessarily reduce consumer risk of exposure to Campylobacter.…”
Section: Discussionsupporting
confidence: 88%
“…This study illustrates the occurrence and antibiotic resistance of Campylobacter in conventionally reared, free-range and backyard chickens. The overall occurrence of Campylobacter obtained in this study (90.6%) is comparable to other reports [20][21][22], including to what has been described in Portugal [23,24]. All the samples from chickens raised in conventional and free-range systems were contaminated, while 73% of samples from backyard chickens were positive, suggesting a lower occurrence of Campylobacter in the latter.…”
Section: Discussionsupporting
confidence: 86%
“…Gentamicin resistance in Campylobacter spp. from poultry is a rare event all over European countries (Carreira et al 2012;De Jong et al 2009;Pérez-Boto et al 2013), probably because it is not used in poultry production. The aph(3´)-III and aadE genes involved in aminoglycoside resistance were identified in some strains.…”
Section: Virulence Determinantsmentioning
confidence: 99%